Settlement prediction of a group of lightweight aggregate (LECA) columns using finite element modelling - Azhani, Zukri; Ramli, Nazir; Shien, Ng Kok (Science Publishing Corporation Inc, 2018)
The method of reinforcing the soft clays with stone columns is the most commonly adopted technique to enhance its load carrying capacity and to reduce settlements. Their performance with respect to bearing capacity is well researched, but the understanding of settlement characteristics still requires extensive investigations. Moreover, no studies have been made to explore the effectiveness of stone columns using Lightweight Expanded Clay Aggregate (LECA) as filler material replacing normal stone/aggregates in order to improve settlement behavior of soft clay. LECA is known as a common lightweight material that have been applied successfully in civil engineering works where weight is an issue because the materials can help to reduce dead loads and lateral forces by more than half in installations over structures and those with soft soils. The purpose of this work is to assess the suitability of reinforcing technique by LECA columns to improve the settlement through finite element. The analysis of performance of LECA column in soft soil improvement was conducted through finite elements methods by using Plaxis 3D commercial software. Based on the results the settlement ratio was reduced as the column length increased until unity at end bearing condition where β = 1.0. It is also observed that bulging was reduced with closer spacing between LECA columns.